Cathodoluminescence imaging of cellular structures labeled with luminescent iridium or rhenium complexes at cryogenic temperatures - Marie Vancová; Radim Skoupý; Eva Ďurinová; Tomáš Bílý; Jana Nebesářová; Vladislav Krzyžánek; Aleš Kolouch; Petr Horodyský (Scientific Reports, 2022)
Abstract We report for the first time the use of two live-cell imaging agents from the group of luminescent transition metal complexes (IRAZOLVE-MITO and REZOLVE-ER) as cathodoluminescent probes. This first experimental demonstration shows the application of both probes for the identification of cellular structures at the nanoscale and near the native state directly in the cryo-scanning electron microscope. This approach can potentially be applied to correlative and multimodal approaches and used to target specific regions within vitrified samples at low electron beam energies.